Tính d ) 7 15 : 5
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, 7×5 + 15 = 35 + 15 = 50
b, 6×5 + 31 = 30 + 31 = 61
c, 22 + 7×4 = 22 + 28 = 50
d, 7×9 + 17 = 63 + 17 = 80
a: \(\dfrac{3}{5}-\dfrac{7}{4}=\dfrac{12}{20}-\dfrac{35}{20}=\dfrac{-23}{20}\)
b: \(\dfrac{4}{5}:\dfrac{-8}{15}=\dfrac{-4}{5}\cdot\dfrac{15}{8}=\dfrac{-60}{40}=\dfrac{-3}{2}\)
c: \(=7+\dfrac{5}{9}-2-\dfrac{3}{4}-3-\dfrac{5}{9}=2-\dfrac{3}{4}=\dfrac{5}{4}\)
d: \(=\dfrac{-3}{7}\left(\dfrac{4}{19}+\dfrac{15}{19}\right)+\dfrac{5}{7}=\dfrac{2}{7}\)
1. a) \(\frac{6}{11}+\frac{7}{5}=\frac{30}{55}+\frac{77}{55}=\frac{30+77}{55}=\frac{107}{55}\)
b) \(\frac{9}{5}-\frac{6}{7}=\frac{63}{35}-\frac{30}{35}=\frac{63-30}{35}=\frac{33}{35}\)
c) \(\frac{11}{2}-3=\frac{11}{2}-\frac{3}{1}=\frac{11}{2}-\frac{6}{2}=\frac{11-6}{2}=\frac{5}{2}\)
d) \(15+\frac{1}{3}=\frac{15}{1}+\frac{1}{3}=\frac{45}{3}+\frac{1}{3}=\frac{45+1}{3}=\frac{46}{3}\)
2. a)\(\frac{3}{7}\cdot\frac{7}{2}=\frac{21}{14}\)
b) \(6\cdot\frac{7}{9}=\frac{42}{9}\)
c) \(\frac{8}{15}\cdot5=\frac{40}{15}\)
d) \(\frac{6}{13}\cdot\frac{26}{2}=\frac{156}{26}\)
Dấu chấm mấy bài trên thay thế cho dấu nhân nhá..
a: \(=\dfrac{-5}{8}+\dfrac{7}{12}=\dfrac{-15}{24}+\dfrac{14}{24}=\dfrac{-1}{24}\)
b: \(=\dfrac{3}{4}-\dfrac{5}{6}+\dfrac{11}{12}=\dfrac{9}{12}-\dfrac{10}{12}+\dfrac{11}{12}=\dfrac{10}{12}=\dfrac{5}{6}\)
c: \(=\dfrac{6}{36}-\dfrac{1}{36}=\dfrac{5}{36}\)
d: \(=\dfrac{5}{12}+\dfrac{5}{12}=\dfrac{10}{12}=\dfrac{5}{6}\)
e: \(=\dfrac{-8}{56}-\dfrac{7}{56}=\dfrac{-15}{56}\)
f: \(=\dfrac{-5}{15}+\dfrac{3}{25}=\dfrac{-25}{75}+\dfrac{9}{75}=\dfrac{-16}{75}\)
a) 5 x 5 + 18
= 25 + 18
= 43
b) 5 x 7 + 23
= 35 + 23
= 58
c) 7 x 7 x 2
= 49 x 2
= 98
d) 15 – 6 x 2
= 15 – 12
= 3
a,2/5+7/10=11/10 b,6/7-5/8=13/56 c,3/5 x 15/8=9/8 d,1/4:3/7=7/12 HT
\(\frac{3}{5}\times\frac{6}{7}+\frac{3}{5}:7+\frac{6}{5}\)
\(=\frac{3}{5}\times\frac{6}{7}+\frac{3}{5}\times\frac{1}{7}+\frac{6}{5}\)
\(=\frac{3}{5}\times\left(\frac{6}{7}+\frac{1}{7}\right)+\frac{6}{5}\)
\(=\frac{3}{5}\times1+\frac{6}{5}\)
\(=\frac{3}{5}+\frac{6}{5}=\frac{9}{5}\)
~ Hok tốt ~
\(\frac{29}{12}:\frac{1}{2}-\frac{5}{12}:\frac{1}{2}-\frac{1}{2}\)
\(=\left(\frac{29}{12}-\frac{5}{12}\right):\frac{1}{2}-\frac{1}{2}\)
\(=2:\frac{1}{2}-\frac{1}{2}\)
\(=4-\frac{1}{2}=\frac{7}{2}\)
~ Hok tốt ~